THE APPLICATION OF HEMP IN BIOECONOMY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Global trends in the world are currently representing a serious incentive to bring ‘green thinking’ to life. This is the case of replacing synthetic materials derived from fossil resources with natural-origin, renewable resources. In the automotive industry and other segments of the manufacturing industry, increasing attention is being paid to the use of natural fibers in the manufacturing of composite materials. For example, flax and hemp fiber, as reinforcing material, is starting to widely replace carbon fiber. It is not just an ecological benefit, but also an important product protecting human health, since the amount of emissions that pollute the environment is minimized. Consequently, that lead to reduced intake by human being of harmful substances that would affect its health status. Existing composite materials used in motor vehicles, produced from carbon fibers, are creating very sharp fracture areas in the event of accidents causing human injury, while materials from natural fiber plants in this case are free from sharp edges at the place of fracture. Raw materials derived from hemp processing are used in the automotive, textile industry, construction (hemp concrete, heat insulation material), energy, biofuel production, arts and design, paper production, food, medicine, etc. This paper covers the main types of products derived from hemp.